BENEFISIASI FISIK PADA PASIR KROMIT KADAR RENDAH MENGGUNAKAN MEJA GOYANG DAN DAVIS TUBE - Ulin Herlina; Fajar Nurjaman; Bambang Suharno; Febriyani Mesah; Muhammad Syahreyzi Pashey Zulqoernain; Muhammad Ridwan Al Fahmi; Yuhelda; Triswan Suseno; Fathan Bahfie; Anton Sapto Handoko; Hafid Zul Hakim; La Ode Arham (Indonesian Mining Journal, 2025)
The rapid growth of the global steel industry has significantly intensified the demand for the metallurgical-grade chromite ore required for ferrochrome production. This surge has led to a depletion of high-grade chromite reserves, necessitating the utilization of low- and medium-grade chromite to support a stable raw material supply for ferrochrome. This research was conducted to determine the characteristics of the ore and to analyze the effects of physical beneficiation processes using shaking table and Davis tube in enhancing the chromium (Cr) grade and the Cr:Fe ratio of low-grade chromite sand from Morowali, Central Sulawesi. The characterization process was conducted using XRF, XRD, and SEM-EDS. Experimental parameters for the shaking table included variations in table inclination and water flow rate, while magnetic separation was analyzed across various electric current intensities. The optimal shaking table test results were achieved at an inclination of 7.5° with a water flow rate of 18 liters/minute. In contrast, the optimal test using the Davis tube was obtained at an electric current of 0.4 amperes (660 gauss). This integrated process successfully increased Cr grade from 8.5% to 20.77% (corresponding to Cr2O3 30.36%) and improved the Cr:Fe ratio from 0.97 to 1.62, achieving a recovery rate of 94.93%.